Preparation of stable micropatterns of gold on cell-adhesion-resistant hydrogels assisted by a hetero-bifunctional macromonomer linker - Sun, Jianguo; Graeter, Stefan V.; Tang, Jian; Huang, JingHuan; Liu, Peng; Lai, YuXiao; Yu, Lin; Majer, Günter; Spatz, Joachim P.; Ding, JianDong (Science China. Chemistry, 2014)
Surface patterning is very useful in biomaterial studies, yet it is not easy to prepare a micropattern with cell-adhesion contrast that is stable in a wet environment. Recently, a platform technique of transfer photolithography was invented to fabricate stable metal microarrays on the surface of a cell-adhesion resistant and mechanically biomimetic poly(ethylene glycol) hydrogel; the linker is the key chemical in such a transfer strategy. This article reports the design and synthesis of a hetero-bifunctional macromonomer linker with a thiol group at one end and an acryloyl group at the other end. The bifunctional linker was characterized by GPC and 1H NMR, and the average number of thiol groups in the bifunctional linker was detected by Ellman’s reagent. The regent stability under wet conditions was also confirmed by the model reactants. The resultant micropatterned surfaces are meaningful for future studies of cell behaviors on mechanically biomimetic matrixes.
Gesehen am 25.08.2020